Camcorder John and Media Narratives: The role of informal communication in participative journalism - Silva, Míriam Cristina Carlos (Brazilian journalism research, 2015)
This article is part of a study supported by the Research Council for the State of São Paulo (FAPESP). It presents the work of an informal communicator called Camcorder John who, despite having only an elementary school education, works informally as a producer in Campina do Monte Alegre, in São Paulo, Brazil. His prospective stories reach regional, national and international media. This study uses interviews and analyses of narratives in order to narrate, describe, organize and analyze some of the practices that include Camcorder John’s stories in media narratives. As its theoretical foundation, the study uses some discussions taken from Benjamin, Sodré, Meditsch, Pontes and Silva. The conclusion is that Camcorder John is a contemporary narrator who has learned both the language of media and the jargon of media professionals; he plays the role of a narrator who is aware of the symbolic power of his narrating.